A feasible process for removal and utilization of CO2 in thermal power plants by MDEA + DMSO scrubbing and Cu/TiO2 photocatalytic reduction. (5th May 2019) - Luo, Qinlan; Cao, Yang; Liu, Zhuhan; Feng, Bin; Zhou, Qulan; Li, Na
Highlights: The absorption and desorption performance of MDEA + DMSO solution are explored. The 2 wt% Cu/TiO2 under 500 °C exhibits the highest photoactivity. A feasible process for simultaneous removal and photoreduction of CO2 is proposed. Abstract: A dynamic system for simultaneous removal of CO2 /SO2 /NO x and desorption of CO2 was developed using N-methyl diethanolamine and dimethyl sulfoxide (MDEA + DMSO) scrubbing. The equilibrium of the absorption-desorption system was achieved as the CO2 absorption rate was approximately equal to the CO2 desorption rate. Then the Cu/TiO2 catalysts under different calcination temperature or with different Cu weight percent were prepared using the modified sol-gel method. Their crystal structures, morphologies, and pore properties were characterized by powder X-ray diffraction, scanning electron microscope, and nitrogen adsorption. The 2 wt% Cu/TiO2 under the calcination temperature of 500 °C exhibits the highest activity for photoreduction of CO2 into CH3 OH with the CH3 OH yield of 12.35 μmol/g/h at 363 K, owing to its smallest crystal size, highest BET surface area and lowest recombination of photogenerated electrons and holes. Meanwhile, a feasible process for the removal and photoreduction of CO2 in thermal power plants using MDEA + DMSO scrubbing and Cu/TiO2 photocatalytic reduction was proposed basing on experimental results. As most of the energy consumption is supplied by solar energy, the process is economical, energy-saving and environmentally friendly.